The effect of faith in intuition on moral judgment: The mediating role of perceived harm - Jiang, Shanshan; Ding, Shang; Ding, Daoqun (Frontiers in Psychology, 2022)
This study aimed to explore the relationship between faith in intuition and moral judgment and the underlying mechanism among Chinese college students using a questionnaire and experimental method. The results showed that levels of faith in intuition predicted more moral wrongness regarding ambiguous hurtful behaviors than unambiguous ones. Additionally, the perceived harm mediated the effect of individuals’ levels of faith in intuition on moral wrongness regarding ambiguous harm behaviors but not regarding unambiguous harm behaviors. The results of this study provide empirical evidence on the relationship between faith in intuition and moral judgment in Chinese culture and have implications for future studies of moral judgments.